Reformulating Water Policy: Reaffirming Farmers’ Rights and Developing Climate-Adaptive Governance Post-Constitutional Court Decision - Hari Kusuma Yuda Tama; Waluyo Waluyo (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
ada